Impacts of Corporate Social Responsibility on Customer Satisfaction in Telecom Industry of Bangladesh - Alam, Naznin; Rubel, Ahsan Kabir (ABC Journal of Advanced Research, 2014)
Worldwide interest is growing day by day about corporate social responsibility (CSR). In the light of the fact stated just now, this paper symbolizes on how customer satisfaction and loyalty are influenced by CSR factors. This paper has investigated the effects of service quality and consumer satisfaction along with corporate social responsibility actions on consumer purchase intentions and further on consumer loyalty. This research was based on primary and secondary data with some structured questionnaire. The primary data has been collected from university students, whereas secondary data was collected from newspapers and website of a related corporation. The data has been analyzed using Factor Analysis. The study found no relationship between awareness of corporate social responsibility and purchase intention. However, significant relationship was observed between service quality and customer satisfaction according to the data. Moreover, there was no relationship between customer satisfaction and purchase intention and purchase intention and consumer retention for telecommunication industry of Bangladesh. The findings of this study are important for corporations and future researchers on corporate social responsibility and consumer behavior in Bangladesh.